Sequential Ultrasonic Spray‐Coating Planar Three Layers for 1 cm2 Active Area Inverted Perovskite Solar Cells. Issue 7 (13th May 2020) - Chou, Li-Hui; Yu, Yu-Tien; Wang, Xiao-Feng; Osaka, Itaru; Wu, Chun-Guey; Liu, Cheng-Liang
Abstract : The sequential deposition of a NiO x hole‐transporting layer, one‐step CH3 NH3 PbI3 perovskite absorber, and blended electron‐transporting layer that comprises [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM) and PNDI(2OD)T2 via automated ultrasonic spray‐coating technique is demonstrated in air for planar inverted p–i–n solution‐processed perovskite solar cells. Films fabricated via laboratory‐sale spin‐coating and industrially compatible spray‐coating process, respectively, are compared with each other to optimize both the film‐coating quality and corresponding device performance. This is validated by the photovoltaic performance of prototype devices with three spray‐coated layers with the active area of 1 × 1 cm 2 . The champion cells achieve a power conversion efficiency of 10.09%, which is one of the highest efficiencies obtained from fully spray‐processed large‐area perovskite solar cells thus far. Furthermore, these results reinforce the feasibility of the spray‐coating methodology for the fabrication of multilayers within perovskite solar cells stack and low‐cost route toward upscaling the manufacturing alternatives to spin coating. Abstract : Sequential ultrasonic spray deposition of the NiO x hole‐transporting layer, CH3 NH3 PbI3 perovskite absorber, and [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM):PNDI(2OD)T2 blend electron‐transporting layer is demonstrated for planar inverted p–i–n perovskite solar cells, achieving the highest power conversion efficiency (PCE) of 10.09%.